Magnetic phase transitions in transition-metal complexes with triazole derivatives - Sugano, T; Kurmoo, M; Blundell, S; Hayes, W; Vilminot, S (2011)
Three divalent transition-metal (Co, Ni and Cu) complexes with the organic anion, 1,2,4-triazolato (tr), as a ligand molecule were prepared by means of hydrothermal syntheses and their magnetic properties were investigated by SQUID magnetometry. The Co(tr)2 and Cu(tr)2 complexes exhibit long range ordering below 8 and 30 K, respectively, while the Ni(tr)2 complex does not show any magnetic phase transition down to 1.8 K. The magnetization isotherms of Co(tr)2 and Cu(tr)2 measured at 2.0 K show hysteresis loops with the coercive fields of 0.5 and 4.7 kOe, respectively. At temperatures higher than about 50 K, the temperature dependence of the magnetic susceptibility of Co(tr)2, Ni(tr)2 and Cu(tr)2 follows the Curie-Weiss law with the Curie constants of 2.95, 0.945 and 0.420 emu K mol-1 and the Weiss temperatures of -62, -74 and -97 K, respectively. These results suggest that the magnetically ordered phases observed in Co(tr)2 and Cu(tr)2 at low temperatures come from antiferromagnetic interactions resulting in canted arrangements of magnetic moments of the transition-metal cations. We discuss here the magnetic interactions in these transition-metal complexes by referring the results of the magnetization measurements. © 2011 Elsevier B.V. All rights reserved.